Asbestos: a chronology of its origins and health effects. Issue 6 (June 1990) - Murray, R
Abstract : The emotionalised subject of asbestos is treated in chronological terms: how the "magic mineral" known in ancient times in Europe and Asia became in the late nineteenth century an important industrial resource of particular interest to the navies of the world; and how its malign effects gradually became apparent during the present century. The media have made asbestos a notorious villain, but it still has properties and applications useful to society if they are properly controlled in the same way as other industrial hazards. One important application is the manufacture of asbestos cement pipes which are a convenient and cheap method of providing water supplies and sewage disposal for developing countries. An appeal is made for prudence and not hysteria in relation to the use of mineral fibres of all types.